A review on photovoltaic and nanogenerator hybrid system - R., Sivasubramanian; C., Aravind Vaithilingam; S. S., Indira; Paiman, Suriati; Misron, Norhisam; Abubakar, Shamsu (Elsevier, 2021)
The increasing prevalence and miniaturization of electronic devices have driven global efforts to develop small-scale, self-sustaining, rugged, and ecologically viable power sources. Nanogenerators, with the ability to scavenge ambient energy from the environment, offer an elegant solution to this need for small-scale power sources. A major route of development for nanogenerators has been in integration with other green energy sources. This article discusses one such integrated power source, namely the photovoltaic and nanogenerator hybrid cells. These hybrid cells have come a long way in terms of mechanical integrity, power output, and efficiency since they were first reported in 2009. Each published instance of photovoltaic and nanogenerator hybrid cell is reviewed systematically and the salient points in each case have been discussed. The article has been concluded with a discussion on the current state of this technology, its limitations, and the avenues for future research.